2004
DOI: 10.1037/0033-295x.111.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Assessing interactive causal influence.

Abstract: The discovery of conjunctive causes-factors that act in concert to produce or prevent an effect-has been explained by purely covariational theories. Such theories assume that concomitant variations in observable events directly license causal inferences, without postulating the existence of unobservable causal relations. This article discusses problems with these theories, proposes a causal-power theory that overcomes the problems, and reports empirical evidence favoring the new theory. Unlike earlier models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(203 citation statements)
references
References 44 publications
(142 reference statements)
6
194
1
2
Order By: Relevance
“…This contrast model, which goes back to Reichenbach (1956), fails to make the correct predictions for certain inductions, and so Cheng (1997) proposed a "power probabilistic contrast" model (the Power PC model) in which the contrast is normalized by dividing it by the base rate for the effect. This factor enters into various computations in order to account for different causal tasks (e.g., Cheng, 1997;Novick & Cheng, 2004). But, even the Power PC model fails to account for all the experimental results (see Lober & Shanks, 2000;Perales & Shanks, 2008).…”
Section: Probabilistic Theories Of Causationmentioning
confidence: 99%
“…This contrast model, which goes back to Reichenbach (1956), fails to make the correct predictions for certain inductions, and so Cheng (1997) proposed a "power probabilistic contrast" model (the Power PC model) in which the contrast is normalized by dividing it by the base rate for the effect. This factor enters into various computations in order to account for different causal tasks (e.g., Cheng, 1997;Novick & Cheng, 2004). But, even the Power PC model fails to account for all the experimental results (see Lober & Shanks, 2000;Perales & Shanks, 2008).…”
Section: Probabilistic Theories Of Causationmentioning
confidence: 99%
“…This term is used to distinguish the definition of causal power in the power PC theory, as the probability with which a CC produces its outcome (Cheng, 1997;Novick & Cheng, 2004), from the definition of causal power in the causal powers theory, as a specific capacity to produce a certain kind of outcome (White, 1989). The latter definition is not probabilistic.…”
Section: Notesmentioning
confidence: 99%
“…But if you find that there was a sprinkler on, you might attribute the wet grass to the sprinkler and discount the probability that the wet grass was caused by rain (Pearl, 1988). Pearl (1988) showed that causal discounting is a normative consequence of reasoning with causal models (see also Novick & Cheng, 2004).…”
Section: Causal Prediction and Causal Attributionmentioning
confidence: 99%
“…The net outcome produced by a set of generative causes accompanied by a preventive cause therefore depends on the order in which causes are combined. Novick and Cheng (2004) distinguished between sequential and parallel integration in certain situations involving interactive causes, arguing that sequential integration is generally the default. By analogy, we derive causal attribution for Case 2 under the assumption that integration of causes is performed sequentially (Carroll & Cheng, 2009).…”
Section: Future Directionsmentioning
confidence: 99%